2013
DOI: 10.1039/c3ta11399j
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of thin-film ceramic electrolytes for high-performance fuel cells

Abstract: This feature article provides a progress review of atomic layer deposition (ALD) for fabrication of oxide-ion as well as proton conducting ceramic fuel cells. A comprehensive analysis of structural, chemical, surface kinetics, and electrochemical characterization results of ALD membranes is also presented. ALD is a surface reaction limited method of depositing conformal, high quality, pinhole-free, uniform thickness nanofilms onto planar or three-dimensional structures. Deposition by one atomic layer at a time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 130 publications
(197 reference statements)
1
55
0
Order By: Relevance
“…It is noteworthy that SOFCs with ALD YSZ electrolytes outperform similar SOFCs using YSZ films prepared by other thin-film techniques [1,6,12,13]. This enhanced performance has been attributed to two properties: the reduced ohmic loss across the ultrathin membrane when used as a freestanding electrolyte in micro-SOFCs, and the greatly improved surface kinetics of nanocrystalline ALD YSZ films [1,6,12].…”
Section: Introductionmentioning
confidence: 93%
“…It is noteworthy that SOFCs with ALD YSZ electrolytes outperform similar SOFCs using YSZ films prepared by other thin-film techniques [1,6,12,13]. This enhanced performance has been attributed to two properties: the reduced ohmic loss across the ultrathin membrane when used as a freestanding electrolyte in micro-SOFCs, and the greatly improved surface kinetics of nanocrystalline ALD YSZ films [1,6,12].…”
Section: Introductionmentioning
confidence: 93%
“…Pt also serves as catalyst for hydrogen dissociation. Then a low-temperature proton conductor yttrium-doped barium zirconate (BYZ) is grown on top that serves as a proton reservoir/ conductor to store/transport protons 27 . Above it, yttria-stabilized zirconia (YSZ) is deposited to serve as a gate insulator at device operation temperature.…”
Section: Doping-induced Phase Transition By LI and Mg Intercalationmentioning
confidence: 99%
“…27 In addition, the self-limiting nature of the ALD ensures that the modification material is uniformly formed on the porous substrate. 28 Yu et al concluded that ALD-added CeO x and SrO had a detrimental effect on the performance of various cathodes. 27 In other studies, ALD Al 2 O 3 was intentionally applied to cathodes in order to examine the relationship between geometric blocking and the performance.…”
mentioning
confidence: 99%